Narrating migrations from Africa and the Middle East a spatio-temporal approach - Breeze, Ruth; Gintsburg, Sarali 1976-; Baynham, Mike 1950- (Bloomsbury Academic, 2022)
"Exploring narratives produced by different groups of MENA and SSA migrants or refugees of various backgrounds, this book focuses on the spatial and temporal aspects of their experiences. Using extensive research of narratives in a variety of different languages, it examines a wide range of accounts of journeys to the host country and memories (or recreations) of "home", the spaces that migrants occupy (or not) in their new country, spaces and times they share with local populations, and different conceptions of space and time across generations. It also considers how feelings surrounding space and time are manifested within these different narratives and their affective-discursive practices. The book takes both a traditional, linear view of migration as well as a multilinear, multimodal approach, presenting the way in which people inhabit multiple real and digital spaces."
Keywords: Literatur; Einwanderer; Mittlerer Osten; Afrika; Africans / Migrations; Middle Easterners / Migrations; African diaspora; Sociolinguistics; Migration, immigration & emigration; Aufsatzsammlung